Teaching a professional foreign language to specialists in various industries - Namestyuk, S. V.; Smolikevych, N. R.; Bytsko, N.; Zaitseva, K. I.; Orlova, О. О.; Орлова, О. О. (International Journal of Higher Education. ‒ 2020. ‒ Vol. 9., No. 7. ‒ P. 59-72, 2020)
This article discusses the main tools and methods of teaching a professional foreign language. Theoretical and practical bases of the organization of the process of introduction and implementation of technologies in teaching foreign languages in higher education are considered and analyzed. The systematization of general trends taking into account domestic and foreign scientific experience is carried out. It also presents the points of view of various scientists on the relevance of studying this topic, formulated recommendations for the introduction of modern effective experience in the practice of foreign language lecturers. The actual task of education, in the trend of globalizing world processes, is teaching a professional foreign language. The development of international cooperation in the fields of education, medicine, natural, technical, and economic sciences requires the study and constant improvement of foreign languages. The existing problems of education require a comprehensive solution. This solution will be achieved using the program-target method. The weakest skill among university students was oral speech. This indicates that conversational skills are a weak point, which is confirmed during observations of classes. A survey of 500 students showed that speaking classes were rated significantly higher than classes for practicing other skills. Thus the aim of the article is a theoretical analysis of scientific approaches of researchers to the problem of teaching a professional foreign language for specialists in various fields.

У статті розглядаються основні інструменти та методи навчання професійної іноземної мови. Розглянуто та проаналізовано теоретичні та практичні основи організації процесу впровадження нових технологій навчання іноземним мовам у вищій школі. Проведено систематизацію загальних тенденцій з урахуванням вітчизняного та зарубіжного наукового досвіду. Також представлені точки зору різних вчених на актуальність вивчення даної теми, сформульовано рекомендації щодо впровадження сучасного ефективного досвіду в практику викладачів іноземних мов. Актуальним завданням освіти в тренді глобалізації світових процесів є викладання професійної іноземної мови. Розвиток міжнародної співпраці в галузі освіти, медицини, природничих, технічних та економічних наук вимагає вивчення та постійного вдосконалення володіння іноземними мовами. Існуючі проблеми освіти потребують комплексного вирішення. Це рішення буде досягнуто за допомогою програмно-цільового методу. Найслабшим умінням серед студентів університету виявилося усне мовлення. Це свідчить про те, що розмовні навички ‒ це слабке місце, що підтверджується під час спостережень за заняттями. Опитування 500 студентів показало, що мовні класи оцінюються значно вище, ніж класи для відпрацювання інших навичок. Таким чином, метою статті є теоретичний аналіз наукових підходів дослідників до проблеми викладання професійної іноземної мови для фахівців різних галузей.
Keywords: professional foreign language; competence-oriented education; professional English; професійна іноземна мова; компетентнісно орієнтована освіта; професійна англійська мова; профессиональный иностранный язык; компетентностное образование; профессиональный английский язык